Effects of Prison Versus Probation in California, 1980-1982 - Petersilia, Joan ([Verlag nicht ermittelbar], 1988)
This study was divided into two phases. The first assessed the effects of different sanctions on separate criminal populations, focusing on probation as a sentencing alternative for felons. The second phase used a quasi-experimental design to address how imprisonment affects criminal behavior when criminals are released. Specific issues included: (a) the effect that imprisonment (vs. probation) and length of time served have on recidivism, (b) the amount of crime prevented by imprisoning offenders rather than placing them on probation, and (c) costs to the system for achieving that reduction in crime.